Continuing professional development in social work - Rutter, Lynne; Brown, Keith (London : Learning Matters, 2013)
There has been a recent focus on how practitioners can engage with continuing professional learning and development. This book is written to support and help busy social workers in front line practice, as well as those in leadership and management roles, to achieve the key aims of continuing professional development (CPD) in a post-qualifying social work context. There are sections on how to engage with CPD at an appropriate level, understanding complex thinking and practices and developing professional reasoning and judgement that can be appropriately recognised and evaluated.
Keywords: Social workers -- In-service training